Potensi Wakaf Saham di Indonesia dan Kendala yang Dihadapi Perspektif Maqashid Syariah - Fitriyah, Alfiyatul; Siti Masriyah; Saroyah, Savinatus; Yuliana, Indah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this study is to identify the challenges and opportunities of share waqf in Indonesia. This study is a review of the literature that draws on a variety of earlier investigations and is bolstered by information from studies that have been disseminated through journals and other scholarly publications from various universities. Researchers employed qualitative descriptive analysis to examine and evaluate the gathered data. The research's findings demonstrate Indonesia's enormous potential for share waqf, which is partly explained by the country's sizable Muslim population. Additionally, there are maslahah in its application that serve as markers of maqashid sharia. However, there are a number of challenges with its implementation, including illiteracy and a lack of knowledge of share waqf. Aside from that, most people still think that fixed assets are the sole way to be able to grant waqf. As a result, share waqf socialization for both the general public and nadzir parties is necessary. Additionally, there has to be more thorough communication and cooperation about share waqf between regulators and participants in the sharia capital market.